Enhancing orthopedic implant bioactivity: refining the nanotopography. (April 2015) - Wang, Guocheng; Moya, Sergio; Lu, ZuFu; Gregurec, Danijela; Zreiqat, Hala
Advances in nanotechnology open up new possibilities to produce biomimetic surfaces that resemble the cell in vivo growth environment at a nanoscale level. Nanotopographical changes of biomaterials surfaces can positively impact the bioactivity and ossointegration properties of orthopedic and dental implants. This review introduces nanofabrication techniques currently used or those with high potential for use as surface modification of biomedical implants. The interactions of nanotopography with water, proteins and cells are also discussed, as they largely determine the final success of the implants. Due to the well-documented effects of surface chemistry and microtopography on the bioactivity of the implant, we here elaborate on the ability of the nanofabrication techniques to combine the dual (multi) modification of surface chemistry and/or microtopography.